2020
DOI: 10.2196/preprints.22125
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Digital Health Platform for Integrated and Proactive Patient-Centered Multimorbidity Self-management and Care (ProACT): Protocol for an Action Research Proof-of-Concept Trial (Preprint)

Abstract: BACKGROUND Multimorbidity is defined as the presence of two or more chronic diseases and associated comorbidities. There is a need to improve best practice around the provision of well-coordinated, person-centred care for persons with multimorbidity (PwMs). Present health systems across the European Union (EU) focus on supporting a single disease framework of care; the primary challenge is to create a patient centric integrated care ecosystem to understand and manage multimorbidity. Pro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The full study protocol, including details on all data collected during the trial and full analysis procedures, can be found in Dinsmore et al [51]. For the purposes of this study, data collection comprised interview data and questionnaire data on usability and user burden at each time point, which coincided with the end of each ARC.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…The full study protocol, including details on all data collected during the trial and full analysis procedures, can be found in Dinsmore et al [51]. For the purposes of this study, data collection comprised interview data and questionnaire data on usability and user burden at each time point, which coincided with the end of each ARC.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…The integration of wearable and medical devices within home Internet of Things (IoT) based solutions were proposed by the European project entitled ProACT (Integrated Technology Systems for ProACTive Patient-Centered Care). ProACT described methods to observe the health condition of elderly people with multi-morbidity, including diabetes, chronic heart failure, and chronic obstructive pulmonary disease (Dinsmore et al, 2018 ; Malavasi et al, 2019 ; Adeniyi et al, 2021 ). However, very few researchers have been examining how to assess the scalability performances of integrating several health applications into a single device to address the complex care needs of patients with multi-morbidity (Dinsmore et al, 2018 ; Waschkau et al, 2019 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…ProACT described methods to observe the health condition of elderly people with multi-morbidity, including diabetes, chronic heart failure, and chronic obstructive pulmonary disease (Dinsmore et al, 2018 ; Malavasi et al, 2019 ; Adeniyi et al, 2021 ). However, very few researchers have been examining how to assess the scalability performances of integrating several health applications into a single device to address the complex care needs of patients with multi-morbidity (Dinsmore et al, 2018 ; Waschkau et al, 2019 ). Further, few authors have proposed several data platforms leveraging big data technology that enable the discovery of emergent multi-morbid patterns and emanating longitudinal risk (Malecki et al, 2020 ; Kishor and Chakraborty, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%